Antioxidant-enriched autologous biogel promoted diabetic wound healing by remodeling inherent posttraumatic inflammatory patterning and restoring compromised microenvironment homeostasis. (29th April 2022) - Yang, Yixi; Wang, Le; Zhou, Yonglin; He, Yijun; Lin, Shaozhang; Zeng, Yuwei; Zhou, Yunhe; Li, Wei; He, Zaopeng; Zhao, Qi; Chen, Lihao; Li, Zijie; et al.
Abstract: Successful wound healing depends on the reconstruction of proper tissue homeostasis, particularly in the posttraumatic inflammatory tissue microenvironment. Diabetes jeopardizes tissues' immune homeostasis in cutaneous wounds, causing persistent chronic inflammation and cytokine dysfunction. Previously, we developed an autologous regeneration factor (ARF) technology to extract the cytokine composite from autologous tissue to restore immune homeostasis and promote wound healing. However, treatment efficacy was significantly compromised in diabetic conditions. Therefore, we proposed that a combination of melatonin and ARF, which is beneficial for proper immune homeostasis reconstruction, could be an effective treatment for diabetic wounds. Our research showed that the utilization of melatonin-mediated ARF biogel (AM gel) promoted diabetic wound regeneration at a more rapid healing rate. RNA-Seq analysis showed that AM gel treatment could restore more favorable immune tissue homeostasis with unique inflammatory patterning as a result of the diminished intensity of acute and chronic inflammation. Currently, AM gel could be a novel and promising therapeutic strategy for diabetic wounds in clinical practice through favorable immune homeostatic reconstructions in the tissue microenvironment and proper posttraumatic inflammation patterning. Graphical Abstract: